2012
DOI: 10.1186/1824-7288-38-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple endocrine neoplasias type 2B and RET proto-oncogene

Abstract: Multiple Endocrine Neoplasia type 2B (MEN 2B) is an autosomal dominant complex oncologic neurocristopathy including medullary thyroid carcinoma, pheochromocytoma, gastrointestinal disorders, marphanoid face, and mucosal multiple ganglioneuromas. Medullary thyroid carcinoma is the major cause of mortality in MEN 2B syndrome, and it often appears during the first years of life. RET proto-oncogene germline activating mutations are causative for MEN 2B. The 95% of MEN 2B patients are associated with a point mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 66 publications
(102 reference statements)
0
28
0
3
Order By: Relevance
“…2,10,11 Genetic analysis of the RET proto-oncogene can be performed in those families affected by MEN2A and MEN2B, in cases of sporadic MTC or HSCR, and allows exact molecular diagnosis of the disease. 12 To the best of our knowledge, this study is the first report of genetic screening of families of the Eastern region of Iran for identification of MEN2A families. We checked all mutation hotspots of the RET proto-oncogene in exons 11, 10, 13, and 8 by direct sequencing to produce reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,11 Genetic analysis of the RET proto-oncogene can be performed in those families affected by MEN2A and MEN2B, in cases of sporadic MTC or HSCR, and allows exact molecular diagnosis of the disease. 12 To the best of our knowledge, this study is the first report of genetic screening of families of the Eastern region of Iran for identification of MEN2A families. We checked all mutation hotspots of the RET proto-oncogene in exons 11, 10, 13, and 8 by direct sequencing to produce reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…Other signs: Other associations have also been reported in MEN2B, including coarse facies, tooth malposition, abnormal feet with a long first toe and an increased space between the 1st and the 2nd toe (Martucciello et al 2012). Underweight, chronic pain and asthenia and delayed puberty can also be seen.…”
Section: Figurementioning
confidence: 89%
“…Forty years ago, Bolande () divided neurocristopathies to simple and complex ones including those with syndromic features. A modification presented by Martucciello et al () adds the possible neoplastic component to both categories. Examples of simple neurocristopathies include albinism and Hirschsprung's disease, whereas neuroblastoma and pheochromocytoma represent examples of simple neurocristopathies with a neoplastic component.…”
Section: Neural Crest‐related Human Diseasesmentioning
confidence: 99%
“…Examples of simple neurocristopathies include albinism and Hirschsprung's disease, whereas neuroblastoma and pheochromocytoma represent examples of simple neurocristopathies with a neoplastic component. Complex neurocristopathies include entities such as neurofibromatosis and multiple endocrine neoplasias 2 and 3 (Martucciello et al ). However, the above classifications do not include craniofacial syndromes of neural crest origin; neural crest‐derived tissues and cells are also frequently affected in Down syndrome, and in animal studies ethanol has been shown to affect cranial neural crest cells with a possible link to human fetal alcohol syndrome (Cartwright and Smith, ).…”
Section: Neural Crest‐related Human Diseasesmentioning
confidence: 99%